Swan Lake: use by migrating waterfowl of the lakes in southern Sukhbaatar, Mongolia - Robertson, Robert A (Wildfowl, 2013)
Lakes in the southern part of Sukhbaatar province, southeast Mongolia, are surrounded by dry steppe to the north and desert to the south, and are likely to be important staging sites for migratory waterbirds. Yet information on the birds’ use of this area is limited. Several lakes, including the Ganga Nuur complex (a Ramsar site), therefore were surveyed in early September 2004 to determine the numbers of wildfowl and shorebirds present. A total of 34 species were recorded, and 4,842 birds counted. These included three species classified by the International Union for Conservation of Nature and Natural Resources (IUCN) as being of global conservation concern: 181 Swan Goose Anser cygnoides (Vulnerable), 17 Black-tailed Godwit Limosa limosa (Near Threatened) and one Asian Dowitcher Limnodromus semipalmatus (also classified as Near Threatened). The counts were undertaken at the start of the migration season, so provide preliminary estimates of site use, but are likely to be much lower than peak counts later in the season. Nevertheless, the results reinforce the view that the lakes provide important habitat for birds in the East Asian flyway. Some land management issues in the area are described.